VALIDASI MODIFIKASI METODE WEIßHAAR UNTUK ANALISIS 3-MCPD ESTER DALAM MINYAK GORENG SAWIT [Validation of Modified Weißhaar’s Method for 3-MCPD Esters Analysis in Palm Oil] - Tanti Lanovia1,2)*; Nuri Andarwulan1,3); Purwiyatno Hariyadi1,3) (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2014)
The 3-monochloropropane-1,2-diol (3-MCPD) and 3-MCPD esters were found in any type of refined vegetable oil -mostly produced during the refining process- and recognized as emerging food contaminants. Several analytical methods have been developed and one of which was a Weißhaar's method. The study aims to validate the modified Weißhaar's method for analysis of 3-MCPD and 3-MCPD esters in refined palm oil. Ion fragments were used for identification and quantification of 3-MCPD and 3-MCPD-d5. 3-MCPD was determined by GC-MS after released from its ester by transesterification with sodium methoxide and derivatized with phenylboronic acid. The validation showed that liniarity response (r=0.994) was observed from a linear regression by using external standard and internal standard at a concentration range of 0.008 and 0.377 µg mL-1. The LOD of the validated method was 0.06 µg g-1 while its LOQ was 0.20 µg g-1, precision (relative standard deviation, RSD) was 6.16%, and accuracy (as percentage of recovery) was in the range of 95.83-113.27%. This results indicated that the modified method was valuable and sensitive for detection of 3-MCPD and 3-MCPD esters. Using the validated method, 3-MCPD esters content of a commercial palm oil sample was determined and calculated as the difference between total 3-MCPD and free 3-MCPD, which was 13.24 µg g-1. Total 3-MCPD content of several palm oils were at a concentration range of 13.94-34.52 µg g-1. These results also showed that there was a correlation between 3-MCPD with diacylglyceride (DAG). Samples with DAG content gave a high test results of 3-MCPD with a coefficient of correlation of r=0.752.